Некои аспекти на претставувањето на телото и телесноста во романот „Книга на смеата и заборавот“ од Милан Кундера (Filološke studije, 2019)
This text examines the models in which the characters of Milan Kundera’s nov- el “The Book of Laughter and Forgetting” construct the idea of body, related to the phonemena of border, mimicry and melancholy. The characters of the novel are constantly watched by the mechanisms of the system, so their bodies are constantly in a metaphorical Panopticon. The instruments of power mark the bodies, inscribe them, retouch them, delete them and liquidate them. Even when they are against the system, the characters of “The Book of Laughter and Forgetting” are becoming, consciously or unconsciously, willingly or unwillingly, part of its machinery, accepting its models of functioning.